2010
DOI: 10.1086/651599
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Follow‐Up of Patients with Acute Hepatitis C Virus Infection in Brazil

Abstract: Background The natural outcome of infection with hepatitis C virus (HCV) varies substantially among individuals. However, little is known about host and viral factors associated with a self-limiting or chronic evolution of HCV infection. Methods From 1 January 2001 through 31 December 2008, a consecutive series of 65 patients from Rio de Janeiro, Brazil, with a well-documented diagnosis of acute HCV infection, acquired via various routes, were enrolled in this study. Patients were prospectively followed up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
2
19
4
3
Order By: Relevance
“…The only correlate of CHCV infection reported by them was low HCV antibody values [46]. The insignificant results in this study may have been due to the small sample size.…”
Section: Discussioncontrasting
confidence: 62%
“…The only correlate of CHCV infection reported by them was low HCV antibody values [46]. The insignificant results in this study may have been due to the small sample size.…”
Section: Discussioncontrasting
confidence: 62%
“…This cohort of patients with acute HCV infection was previously evaluated by clinical and laboratory parameters [31]. Patients with undetected HCV RNA in three consecutive tests within 12-months of follow-up were considered as having spontaneous viral clearance.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with undetected HCV RNA in three consecutive tests within 12-months of follow-up were considered as having spontaneous viral clearance. Further details were described elsewhere [31]. The inclusion criteria for chronic hepatitis C patients were: detectable anti-HCV antibodies with detectable serum, HCV RNA for 6 months of follow up, and a liver biopsy with characteristics of chronic HCV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Fourthly, we assumed that only two parameters were associated with spontaneous viral clearance and were considered in the model (IL28B genotype and whether the patient was symptomatic or asymptomatic). Indeed, although Hofer et al suggested that repeated measurements of serum viral load are associated with spontaneous viral clearance [9], many other studies could not conclude that HCV RNA baseline levels or kinetics are a predictor of HCV clearance [34,40,41]. In addition, other authors show that HCV RNA levels fluctuate in the setting of acute HCV infection, which may limit prediction of viral clearance [38,42].…”
Section: Discussionmentioning
confidence: 99%